Foundation Controversy as a Tool for Misuse of Loopholes Funds in Foundation Settings in Indonesia - Febrianty, Yenny; Suciani Putri, Viorizza; Pransisto, Johamran; Heridah, Andi; Kasim, Aksah (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
This study analyses the use of foundations as mechanisms for financial diversion and highlights the legal shortcomings in the regulation of foundations in Indonesia, leading to insufficient oversight and public accountability. Recent incidents, including the Aksi Cepat Tanggap Foundation (ACT) and the PPATK's disclosures regarding 176 philanthropic institutions, suggest that certain foundations function as front organisations to conceal or misdirect funds from unclear sources. This study utilises a normative juridical methodology, employing statutory, conceptual, and case approaches. It focusses on examining Law Number 28 of 2004 concerning Foundations, its derivative laws, and the management practices of social funds in charitable organisations. The findings of the study reveal that foundation supervision in Indonesia is insufficient, as the supervisory body provides guidance without audit authority, and external oversight by the Ministry of Law and Human Rights and the Ministry of Social Affairs is restricted to administrative functions lacking substantive audits. Agency fragmentation, insufficient consequences, and the lack of public disclosure requirements increase the likelihood of legal form misuse. The supervisory system necessitates reform via the alteration of foundational rules, the implementation of digital public audits, and the strengthening of fiduciary obligations and good governance principles within positive law. This research highlights the necessity of integrating legal standards with social norms to establish governance defined by transparency, accountability, and integrity, thereby restoring public trust in non-profit organisations in Indonesia